What is the decision making process of entrepreneurs' implementation of MCS software, and how are external consultants engaged and used in the process? How does this engagement affect an ongoing relationship between the two? : an exploratory study, [a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Accountancy at Massey University, Palmerston North, New Zealand] - Molotsky, Steven (Massey University, 2011)
Abstract not available
Keywords: Small business; Business consultants; Management information systems; Entrepreneurs; Accountancy